2009
DOI: 10.1038/onc.2009.130
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 secreted from adipose stromal cells promotes migration and invasion of breast cancer cells

Abstract: Excessive adiposity has long been associated with increased incidence of breast cancer in postmenopausal women, as well as with increased mortality of breast cancer, regardless of menopausal status. While adipose tissue-derived estrogen contributes to obesity-associated risk for estrogen receptor (ER)-positive breast cancer, the estrogen-independent impact of adipose tissue on tumor invasion and progression remains to be elucidated. Here we show that adipose stromal cells (ASCs) significantly stimulate migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
236
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(253 citation statements)
references
References 49 publications
10
236
1
3
Order By: Relevance
“…For p38-MAPK enzymatic assays (enzyme sourced from either Millipore or Roche), 33 P-ATP radiometric filter binding (Millipore MAPH plates) was used with an EGFR peptide substrate, KRELVEPLTPSGEAPNQALLR (Multiple Peptide Systems), and 100 mmol/L (p38a) or 20 mmol/L (p38b, p38g) ATP run under linear velocity conditions. LY2228820 was also tested against a panel of enzymatic kinase assays (internal assays and Merck Millipore KinaseProfiler; ref.…”
Section: Kinase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…For p38-MAPK enzymatic assays (enzyme sourced from either Millipore or Roche), 33 P-ATP radiometric filter binding (Millipore MAPH plates) was used with an EGFR peptide substrate, KRELVEPLTPSGEAPNQALLR (Multiple Peptide Systems), and 100 mmol/L (p38a) or 20 mmol/L (p38b, p38g) ATP run under linear velocity conditions. LY2228820 was also tested against a panel of enzymatic kinase assays (internal assays and Merck Millipore KinaseProfiler; ref.…”
Section: Kinase Assaysmentioning
confidence: 99%
“…Furthermore, secretion of CXCL8 by both the tumor and TME increases proliferation of ovarian cancer cells in vitro and in vivo (30,32). IL-6, secreted from adipose stromal cells to promote migration and invasion of breast cancer cells (33), likely requires p38 MAPK because its direct substrate, MK2, contributes to IL-6 mRNA stabilization (34). Finally, from the perspective of immune surveillance, activation of p38 MAPK is associated with enhanced dendritic cell tolerance during melanoma progression (35).…”
mentioning
confidence: 99%
“…Tumor-promoting effects of adipocytes have been linked to their secretion of adipokines, hormones, and growth factors into the cancer microenvironment, which enhance cancer cell migration and invasion (50). A study conducted by Walter and colleagues revealed that normal adipose cells stimulated the migration and invasion of estrogen receptor (ER)-negative breast cancer cells (51). This effect was mediated via a cytoskeletal element, cofilin-1, and it's regulation of IL-6 secretion in adipocytes (51).…”
Section: Omentum-derived Adipocytesmentioning
confidence: 99%
“…A study conducted by Walter and colleagues revealed that normal adipose cells stimulated the migration and invasion of estrogen receptor (ER)-negative breast cancer cells (51). This effect was mediated via a cytoskeletal element, cofilin-1, and it's regulation of IL-6 secretion in adipocytes (51). Another study revealed that during coculture with breast cancer cell lines, adipocytes acquired an activated phenotype, characterized by increased production of proteases and cytokines, IL-6 and IL-1b, as well as delipidation and a loss of adipocyte-associated markers (50).…”
Section: Omentum-derived Adipocytesmentioning
confidence: 99%
“…3D). To analyze whether the effect of activated STAT3 on PML gene expression is mediated via secreted IL6, BJ-conditioned medium was depleted for IL6 with a specific antibody (51). The effectiveness of IL6 depletion was verified utilizing growth dependence of murine hybridoma B9 cells on human IL6 (46).…”
Section: Pml Nbs Pml Protein and Transcript Level Are Modulated Inmentioning
confidence: 99%